Efektivitas Undang-Undang Nomor 10 Tahun 2009 tentang Kepariwisataan terhadap Pelaku Pariwisata - I Made Agus Setiawan; Kadek Mery Herawati; I Gusti Ngurah Aristiawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the effectiveness of Law Number 10 of 2009 on Tourism in relation to tourism actors in Indonesia. The enactment of this law is intended to provide legal certainty, protection, and development opportunities for business actors, tourists, and the community in supporting sustainable tourism development. The research employs a normative-empirical legal method with statutory and conceptual approaches. Data were collected through literature review and field observation to assess the extent to which the legal norms contained in the Tourism Law are implemented in practice. The findings reveal that the law has provided an important normative framework for the recognition of rights, capacity building, and protection of tourism actors. Nevertheless, structural challenges such as limited access to capital, low human resource competence, and the suboptimal implementation of legal protection and social security remain significant obstacles. Therefore, strengthening strategies are required through digitalization, training and certification, facilitation of MSMEs, and pentahelix synergy involving government, academia, business actors, communities, and the media. Through these measures, the implementation of the Tourism Law is expected to foster a tourism ecosystem that is competitive, inclusive, and sustainable at the local, national, and global levels.